Shaping urban futures in Mongolia : Ulaanbaatar, dynamic ownership and economic flux - Plueckhahn, Rebekah (Economic exposures in Asia., 2020)
Shaping Urban Futures in Mongolia discusses the lived experience of urban development, redevelopment and change in Ulaanbaatar, Mongolia.